Ethnobotany of Medicinal Plants in Bromo Tengger Tribe Area, Bromo Tengger Semeru National Park - Serafinah Indriyani Indriyani; Jati Batoro; Gustini Ekowati (Natural B, Journal of Health and Environmental Sciences, 2012)
The research on use of various plants for medical purposes was undertaken in Tengger tribe area, Bromo Tengger Semeru National Park (BTSNP). The objectives of the research were to give information about species and potency of medicinal plants. Ethno-direct sampling was done through directly or semi-structural interview to the ordinary peoples, traditional leader and traditional therapist. The result of study showed that there were 98 species of medicinal plants that used by Tengger purwoceng (Pimpinella pruatjan), krangean (Abrus laevigatus), adas (Foeniculum vulgare), kayu ampet (Astronia macrophylla), pulosari (Alyxia reinwardtii), pronojiwo (Euchresta horsfieldii), sempretan, dringu (Acorus calamus) dan jamur impes were endemic grow in BTSNP. Tengger tribe did not cultivate the medicinal plants by themselves but seeking it in BTSNP forest.